Storytelling, the scale of persuasion and retention: A neuromarketing approach. (July 2020) - Hamelin, Nicolas; Thaichon, Park; Abraham, Christopher; Driver, Nicholas; Lipscombe, Joe; Pillai, Jayarethanam
Abstract: Persuasive storytelling is an essential tool for propagandists, publicists, and corporations. In this research, storytelling styles have been examined for their effectiveness in terms of attitude change and retention. Two groups of respondents were asked to read two short, fictional texts about a chosen corporation's positive action toward the environment. One story was written using words from the Micro-WNOp corpus to elicit positive emotions (Story 1), while the other was written with a more cognitive approach (Story 2). Biometrics data, eye tracking, facial expression analysis, and galvanic skin responses (GSR) were recorded while respondents read the texts. Heat maps and area of interest analysis show that although the affective story was faster and more effective at changing respondents' attitudes, the cognitive approach resulted in longer-lasting attitudinal change. As such, affective stories may lead to more immediate shifts in attitude, but cognitive stories result in deeper elaboration and subsequently better retention.